Collaboration between School and Parents for Students’ Better Future by Parenting: An Ethnographic Approach - Sukamto, Ismu; Fauziah, Puji Yanti; Wibawa, Lutfi; Kumullah, Rahmah (JURNAL INOVATIF ILMU PENDIDIKAN, 2023)
Parenting programs have been shown to improve children's behavior. Therefore, the implementation of parenting programs in schools needs to be revealed as a reference for schools to more easily implement them in the school environment. This research uses an ethnographic approach. A sample of one school in Bandar Lampung City was determined using purposive sampling techniques with the criteria that the school had implemented a parenting program. Research data were collected using interviews, observation, and documentation techniques. Data analysis is carried out using thematic analysis, which includes seven phases. Triangulation techniques are used as data validity tests. The findings of this study show that the parenting program was implemented through seminars, teacher-parent collaboration through contact books, guest teachers by parents, sharing short videos through social media, and the presence of BK teachers at school. Thus, it can be concluded that the parenting program is getting optimal by realizing collaborative activities between schools and parents in student learning activities.Keywords: Parenting, elementary school